Algoritmos exatos e heurísticos para o problema da diversidade máxima - Oliveira, Lucas Vinicius Amaral de (2017)
In this work, we suggest Branch-and-Cut algorithms and Lagrangian heuristics for the Maximum Diversity Problem. We use a standard formulation reinforced by some valid inequalities for the problem. These are dynamically dualized in the heuristics and used as cuts in the exact methods. To separate them efficiently, we propose some heuristic procedures. In addition, we perform computational tests and compare our exact and heuristics methods with those found in the literature for the problem.